COMMENTS TO THE NEW REGULATORY DOCUMENTS OF SANITATION (Municipal economy of cities. Series: «Economy science», 2013)
Estimations of new standard documents in the field of the water removal are given, installed in Russia on January, 1st, 2013. Is shown that the successful decision of problems of protection of water objects probably only under condition of the decision of a complex of scientific, legal, legislative, standard and financial problems. In this business it is necessary to make use of positive experience of other countries.